2020
DOI: 10.1021/acs.jpcc.9b11037
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Size-Dependent Interaction between Ethylene and CuCl2 Clusters Supported via γ-Alumina

Abstract: Alumina-supported copper chloride serves as an industrial catalyst for ethylene oxychlorination, resulting from its high activity and selectivity. A better understanding of the detailed active site structure and reaction mechanism is highly desired. The present work aims to explore the dependence of the structure of active sites and the adsorption of ethylene on differently sized (CuCl 2 ) n (n = 1−4) clusters supported by γ-Al 2 O 3 . The effect of the support facets (i.e., ( 110) and ( 100) surfaces) on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…CuCl 2 reacts with C 2 H 4 in the reduction step (eq ) to form EDC and CuCl in principle. It is consistent with the observation of density functional theory (DFT) , and kinetic studies, , where ethylene first attracted two Cl atoms from CuCl 2 with a very low energy barrier. However, CuCl 2 is rapidly converted to an intermediate instead of CuCl, as shown in Figure b.…”
Section: Results and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…CuCl 2 reacts with C 2 H 4 in the reduction step (eq ) to form EDC and CuCl in principle. It is consistent with the observation of density functional theory (DFT) , and kinetic studies, , where ethylene first attracted two Cl atoms from CuCl 2 with a very low energy barrier. However, CuCl 2 is rapidly converted to an intermediate instead of CuCl, as shown in Figure b.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The intermediate should be Cu species with an oxidation state between CuCl 2 and CuCl. The coordination numbers of Cu with the Cl were found to be 4 and 2 for CuCl 2 and CuCl, respectively. , The reaction of CuCl 2 with C 2 H 4 removed the lattice Cl to form Cl vacancy on CuCl 2 catalysts. DFT study suggested that CuCl 2 with vacancy could have coordination numbers of 3 and 2 for low and high concentrations of Cl vacancy, respectively. , Lattice Cl is rather mobile in CuCl 2 and can rapidly redistribute on the surface .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations